Analisis Pengaruh Tingkat Pendidikan, Keterampilan, Upah Dan Umur Terhadap Lama Mencari Kerja Pada Tenaga Kerja Terdidik Di Kabupaten Manokwari - Makaria Mayoni; Yuyun P. Rahayu; Marcus R. Maspaitella (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
This study aims to find the variables that most influence the length of time to get a proper job for an educated workforce. Some influencing factors based on previous research which are used as independent variables include the level of education, skills, wages and age. This research hypothesises is that simultaneously and partially, the four variables affect the length of time seeking for a job. A regression analysis had been conducted to prove this hypothesis. This research used 100 educated labour as respondents in Manokwari Regency. The result shows that simultaneously, at a 90% confidence level, all independent variables influence the length of time looking for a job. Meanwhile, partially, only the skill variable significantly influences it.